EFEKTIVITAS MODEL PEMBELAJARAN GROUP INVESTIGATION TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI JOMBLANGAN - Ahmad Tafaul Rosyid; Istiqomah Istiqomah (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study descriptively aims to determine the tendency of mathematics learning outcomes of class V students of Jomblangan Elementary School using the investigation and expository group model. The study was conducted at Jomblangan State Elementary School with a population of all class V students consisting of 2 classes the total are 56 students. The sample was taken by simple random sampling technique. The data collection techniques used were documents for initial abilities and tests to measure student mathematics learning outcomes. The instrument testing used uses the trial system. Data analysis techniques were calculated using the t-test, and previously carried out the analysis of the requirements analysis, including balance test, normality test, and variance homogeneity test. Descriptive research results show the tendency of mathematics learning outcomes of class V students of Jomblangan State Elementary School using the investigation group learning model including the high category with an average value of 72,800, while those using the expository learning model are in the moderate category with an average of 53,231. Comparatively, the hypothesis testing shows that the group investigation learning model is better than the expository learning model seen from student learning outcomes. This is indicated by the t-test obtained by count = 4.362 and t table = 1.645 because of the tcount> table. In other words, it can be concluded that the group investigation learning model is more effective than the expository learning model for the results of mathematics learning in the fifth-grade students of Jomblangan Elementary School.